2007
DOI: 10.1186/1471-2156-8-15
|View full text |Cite
|
Sign up to set email alerts
|

PRNP promoter polymorphisms are associated with BSE susceptibility in Swiss and German cattle

Abstract: Background: Non-synonymous polymorphisms within the prion protein gene (PRNP) influence the susceptibility and incubation time for transmissible spongiform encephalopathies (TSE) in some species such as sheep and humans. In cattle, none of the known polymorphisms within the PRNP coding region has a major influence on susceptibility to bovine spongiform encephalopathy (BSE).Recently, however, we demonstrated an association between susceptibility to BSE and a 23 bp insertion/deletion (indel) polymorphism and a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 28 publications
5
77
3
Order By: Relevance
“…For 12-bp indel locus, the allele 'I' frequency was higher than allele 'D' frequency in all studied breeds population, which was in contradiction to the previous reported results in US sires, Mongolia native and other cattle breeds population (Seabury et al 2004;Shimogiri et al 2010). Notably, allele 'I' at these two locus was higher in Chinese indigenous breeds, and previous reports revealed that the 12-bp insertion and 23-bp insertion polymorphisms all increased the resistance to BSE (Sander et al 2005;Juling et al 2006;Haase et al 2007;Xue et al 2008;Msalya et al 2010). Moreover, to date, occurrences of BSE have never been detected in China.…”
Section: Discussioncontrasting
confidence: 56%
“…For 12-bp indel locus, the allele 'I' frequency was higher than allele 'D' frequency in all studied breeds population, which was in contradiction to the previous reported results in US sires, Mongolia native and other cattle breeds population (Seabury et al 2004;Shimogiri et al 2010). Notably, allele 'I' at these two locus was higher in Chinese indigenous breeds, and previous reports revealed that the 12-bp insertion and 23-bp insertion polymorphisms all increased the resistance to BSE (Sander et al 2005;Juling et al 2006;Haase et al 2007;Xue et al 2008;Msalya et al 2010). Moreover, to date, occurrences of BSE have never been detected in China.…”
Section: Discussioncontrasting
confidence: 56%
“…There is also as yet no other PrP protein polymorphism in cattle that can be associated with BSE. However the recently discovered PrP promoter polymorphisms may be associated with susceptibility to BSE in British and German herds [41,56]. The main effect is with the 12 bp deletion allele (12del).…”
Section: Bse In Cattlementioning
confidence: 99%
“…Previous reports revealed that the 12-bp insertion and 23-bp insertion polymorphisms all increased the resistance to BSE, while the 12-bp deletion polymorphism resulted in the increasing expression of PrP, and which resulted in higher susceptibility to prion diseases (Sander et al 2005;Juling et al 2006;Haase et al 2007;Xue et al 2008). The expression level of PrP had a negative relationship with the resistance to BSE, when the expression level of PrP was increasing, while the resistance would be decreasing.…”
Section: Discussionmentioning
confidence: 98%
“…Until now, many polymorphisms of PRNP had been identified in cattle. Previous reports have shown that several PRNP polymorphisms were associated with resistance to BSE in cattle (Sander et al 2005;Haase et al 2007;Kashkevich et al 2007). In particular, a 23-bp in-del polymorphism within the PRNP promoter region and a 12-bp in-del polymorphism within intron 1 seemed to affect the binding sites for the transcriptional factors RP58 and SP1, respectively, and might influence PRNP expression (Sander et al 2004;Sander et al 2005;Xue et al 2008).…”
Section: Introductionmentioning
confidence: 99%